Maoist people's war and the revolution of everyday life in Nepal - Zharkevich, I (Cambridge University Press, 2019)
This book is an ethnography of social change and norm-remaking brought about by the Maoist People’s War in Nepal between 1996 and 2006. Drawing on long-term fieldwork with people in the former Maoist heartland, including both committed Maoist revolutionaries and ‘reluctant rebels’, it explores how a remote Himalayan village was forged as the centre of the Maoist rebellion, how its inhabitants coped with the situation of war, how they came to embrace the Maoist project and maintain ordinary life during war. Contrary to the dominant narrative, even in the Maoist capital, hailed as a village of resistance, a lot of ordinary people were only ‘reluctant rebels’ who supported the Maoists because of kinship ties, moral solidarity, and compliance with the Maoist regime of governance. By focusing on the relational side of the Maoist movement – kinship ties between ordinary villagers and guerrillas, fraternal and affective bonds within the Maoist movement – the book explores the social processes and relationships through which the People’s War became possible. The book illuminates how the everyday became a primary site of revolution in Nepal: of crafting new subjectivities, normalizing previously transgressive norms, such as beef-eating and inter-caste commensality, and reconfiguring the ways people act in and think about the world. Revolution in Nepal came about not as a result of war, but rather in the process of war, with the praxis of revolutionary modes of sociality and ‘embodied change’ being key to transforming people’s practical consciousness. Rather than being simply an outcome of the Maoist policies or ideas, much of the change was a result of embodied experiences of radically new ways of relating across caste, class and gender divides. By having recreated their everyday practice—often as part of the exceptional times of war and rules that apply in times of crisis—people in the Maoist base area transformed not only their values, but also the rigid social hierarchies structuring Nepali society.